Worstelen met gender en de biografie: een themarecensie - Mineke Bosch (BMGN: Low Countries Historical Review, 2012)
Wrestling with Gender and Biography: A Thematic Review In her ‘very short introduction’ to biography of 2009, Hermione Lee notices that although much has been said and done about gender and biography, ‘the challenge remains how best to tell the stories of the increasing number of women in the public sphere [...]’. In this review essay Mineke Bosch tries to answer this question by analysing two recent biographies of professional women: the first minister of state in the Netherlands, Marga Klompé, by Gerard Mostert, and sociologist and politician Hilda Verwey-Jonker by Margit van der Steen. Comparing the two, Bosch states that Mostert repeats old truths and stereotypes about successful women in the public sphere with his conclusion that Klompé was a meddler and a fiercely dominant busybody, and that precisely these character traits made it possible for her to capitalise on her ambitions and become one of the boys. Margit van der Steen shows a more subtle understanding of gender as an analytical category. She shows how Hilda Verwey-Jonker wrestled with being a woman in a man’s world, changing her (gender) performance several times in parallel with her social and professional context. Both biographies, however, could have profited more from recent biographical theory in which the emphasis is more on ‘doing identities’ than ‘being one/self’.